GAYA BAHASA SINDIRAN SEBAGAI BENTUK KOMUNIKASI TIDAK LANGSUNG DALAM BAHASA LAIYOLO - Nurlina Arisnawati (Balai Bahasa Sumatera Utara, 2020)
The use of satire language in Laiyolo people's lives is quite intense. This is because it is motivated by the nature of the people of Laiyolo who do not like to be frank by sticking to the attitude of tasipakaito, 'humanizing each other' or posianggarangi 'mutual respect'. Therefore, Laiyolo people use satirical language as a form of indirect communication to people who have done something that is not pleasant. This paper discusses figure of speech of satire as a form of indirect communication in Laiyolo. The purpose of this paper is to describe the use of satirical as a form of indirect communication in Laiyolo. The method used is descriptive qualitative, the data collection technique through observational, conversation, and recording. The results of the data analysis show that satirical, namely irony, cynicism, and sarcasm. These three satirical are basically contrary to the principle of cooperation and the principle of politeness. However, these three satirical are considered safer spoken than criticizing, insulting, berating, mocking, and so on.